2009
DOI: 10.4038/gmj.v14i1.1169
|View full text |Cite
|
Sign up to set email alerts
|

Branching pattern of the femoral artery at the femoral triangle: a cadaver study

Abstract: The proper knowledge of the course and ramification of the blood vessels of the lower limbs is very important for surgeons and interventional radiologist. This is because the lower limb arteries are commonly involve with peripheral occlusive arterial diseases and the femoral artery at the femoral triangle is widely used for certain clinical procedures like arterial catheterization. Although there are several studies on the branching pattern of the femoral artery in the femoral triangle the Sri Lankan studies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 2 publications
5
34
2
Order By: Relevance
“…In disagreement with the results of present study, different ranges of the distance were obtained in literature: 31-40 mm in right limbs and 41-50 mm in left limbs [8]; 55 mm on right side and 45 mm on left side [17]; commonly between 31-40 mm [2] and its mean was 42 mm [15], 44 mm [18], 32 mm [16] and its normal range was 35-40 mm [21]. Awareness of the original site and distance of PFA is important for prevention of iatrogenic injuries that may occur during the diagnostic or therapeutic procedures in the femoral region.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In disagreement with the results of present study, different ranges of the distance were obtained in literature: 31-40 mm in right limbs and 41-50 mm in left limbs [8]; 55 mm on right side and 45 mm on left side [17]; commonly between 31-40 mm [2] and its mean was 42 mm [15], 44 mm [18], 32 mm [16] and its normal range was 35-40 mm [21]. Awareness of the original site and distance of PFA is important for prevention of iatrogenic injuries that may occur during the diagnostic or therapeutic procedures in the femoral region.…”
Section: Discussioncontrasting
confidence: 99%
“…In agreement with the results of present study, Dixit et al [8] found this origin pattern in 28.5% of the limbs. However, a higher incidence rates were recorded in the literature, 53.3% [11], 46.9% [15], 46.1% [17] and 44.6% [20]. Moreover, the PFA originated from the lateral aspect of FA in 20% of the limbs with no side or sex differences in the present study and this in agrees with Siriporn et al [20] who found this pattern in 21.4% in Thailand population.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The mean distance of PFA origin from the femoral artery in our study was 4.31 cms, which was similar to study by Siddharth P et al [3] who reported it to be 4.4 cms. MB Samarawickrama et al [10] observed distance of origin of PFA to be 5 cms and Mamatha et al [11] found it to be 3.9 cms. In the present study high origin of PFA was noted 2 cms from the mid inguinal point.…”
Section: Resultsmentioning
confidence: 99%